2008
DOI: 10.1038/sj.ki.5002620
|View full text |Cite
|
Sign up to set email alerts
|

Automated peritoneal dialysis as a lifesaving therapy in an emergency room: Report of four cases

Abstract: The present article describes four cases of patients with chronic kidney disease who arrived at the emergency room in critical condition, needing acute dialysis for severe hyperkalemia and metabolic acidosis. These four patients were treated acutely with automated peritoneal dialysis (APD) using a Tenckhoff catheter placed percutaneously at the bedside in the emergency room. All patients were discharged in good condition and with APD as their chronic renal replacement therapy (RRT). APD is a RRT, that may be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Ilabaca-Avendaño et al (35) described 4 patients with chronic kidney disease and acute metabolic acidosis who were treated successfully with APD. Another paper published by Vaziri et al (36) dealt with a subset of patients with severe lactic acidosis who did not respond to large amounts of intravenous sodium bicarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…Ilabaca-Avendaño et al (35) described 4 patients with chronic kidney disease and acute metabolic acidosis who were treated successfully with APD. Another paper published by Vaziri et al (36) dealt with a subset of patients with severe lactic acidosis who did not respond to large amounts of intravenous sodium bicarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…In two prospective studies from France and India, urgent initiation of APD was proven an efficacious dialysis modality [104,105]. Moreover, APD has been performed as a frontline urgent dialysis therapy option with good results [106]. Another study compared urgent-start APD with urgent-start CAPD (1-3 days after catheter insertion) and concluded that during the initial 9-day break-in period, APD resulted in better solute clearance, had similar complications but also led to a significant decline in serum albumin.…”
Section: Urgent Start Of Pdmentioning
confidence: 99%
“…A 2008 report from a hospital without access to HD equipment described 3 critically ill patients not previously on dialysis with serum potassium values greater than 8.0 mEq/L who were successfully treated with acute PD. Emergency medicine residents were trained to insert Tenckhoff catheters percutaneously, and nurses were taught to use a PD cycler [10]. Our case extends the literature to demonstrate that a patient already established on PD can be effectively treated for severe hyperkalemia without HD if temporizing measures and exchanges alone are initiated early.…”
mentioning
confidence: 77%